Strategies to promote the adoption of digital payment platforms in microenterprises in the northern sector of Guayaquil - Vera, Raquel; Yong, Linda (EASI: Engineering and Applied Sciences in Industry, 2025)
This article aims to identify strategies to expand the adoption of digital payment platforms in microenterprises in northern Guayaquil, highlighting their importance in business modernization and economic growth within e-commerce. The exploratory-descriptive and propositional research analyzed barriers such as the preference for cash, lack of knowledge, and economic and technological limitations. Through a survey of 278 microentrepreneurs, it was found that only 34.4% use digital platforms, mainly Payphone and Kushki. The benefits of adoption include greater security, increased sales, and better financial organization. Strategies such as educational campaigns, financial incentives, technological improvements, and generating trust are proposed. The research concludes that collaboration between the public, private, and academic sectors is essential to facilitate the digital transition and enhance business competitiveness in Guayaquil.
Keywords: Digital payment platforms; Microenterprises; E-commerce; Inclusive digitalization; Estrategies